Intervensi Oral Care pada Pasien Anak dengan Resiko Aspirasi Gaucher Disease: Case Report - Ayene Refina; Sri Hendrawati (Malahayati Nursing Journal, 2025)
ABSTRACT Gaucher disease (GD) is a rare disease characterized by a deficiency of the enzyme Glucocerebrosidase, resulting in a buildup of fatty substances which can damage body organs, one of which is neurological disorders. With neurological disorders, the patient will be at risk of aspiration so it is necessary to install a Nasograstric Tube (NGT). NGT care needs to be carried out including maintaining the moisture of the oral mucous membrane. The aim of this study was to identify oral care interventions in reducing the degree of damage to the oral mucous membranes in pediatric patients with Gaucher disease. This research uses a case report method with a nursing care approach. The instrument used was BOAS (Back Oral Assessment Score) which was assessed on the first and last day of intervention. This research was conducted on An. A is 25 months old and is being treated at RSUP Dr. Hasan Sadikin Bandung. Obtained subjective data from An. A has been using an NGT for two months and plans to go home with the NGT still installed, An's oral mucosa. A is dry, and there are reddish black lesions on the lower lip. The nursing diagnosis in the case was the risk of aspiration, while the intervention carried out was oral care and honey which was given every eight hours for three days with a duration of 15-20 minutes. Based on the research results, it was found that oral care and honey can reduce the degree of damage to the oral membranes in children with a BOAS score of 11 before the intervention and after the intervention to 9. The researcher's suggestion for nurses as care givers is to apply oral care and honey to pediatric patients to maintain the moisture of the mucous membranes. orally due to long-term use of NGT. Keywords: Children, Impaired Skin Integrity,  Gaucher Disease, Oral Care  ABSTRAK Gaucher disease (GD) merupakan suatu penyakit langka yang ditandai dengan adanya kekurangan enzim Glucocerebrosidase, sehingga terjadi penumpukan zat lemak yang dapat merusak organ tubuh salah satunya gangguan neurologis. Dengan adanya gangguan neurologis, pasien akan mengalami resiko aspirasi sehingga perlu dilakukan pemasangan Nasograstric Tube (NGT). Perawatan NGT perlu dilakukan termasuk  menjaga kelembaban membran mukosa oral. Tujuan penelitian ini untuk mengidentifikasi intervensi oral care dalam menurunkan derajat kerusakan membran mukosa oral pada pasien anak dengan gaucher disease. Penelitian ini menggunakan metode case report dengan pendekatan asuhan keperawatan. Instrumen yang digunakan yaitu BOAS (Back Oral Assessment Score) yang dikaji pada hari pertama dan terakhir intervensi. Penelitian ini dilakukan pada An. A berusia 25 bulan dan dirawat di RSUP Dr. Hasan Sadikin Bandung. Didapatkan data subjektif An. A sudah menggunakan NGT selama dua bulan dan rencana akan pulang dengan NGT yang masih terpasang, mukosa oral An. A kering, dan terdapat lesi berwarna hitam kemerahan di bibir bawah. Diagnosis keperawatan pada kasus yaitu resiko aspirasi, sedangkan intervensi yang dilakukan yaitu oral care dan madu yang diberikan setiap delapan jam sekali selama tiga hari dengan durasi 15-20 menit. Berdasarkan hasil penelitian didapatkan bahwa oral care dan madu dapat mengurangi derajat kerusakan membran oral  pada anak dengan skor BOAS 11 sebelum intervensi dan setelah intervensi menjadi 9. Saran peneliti untuk perawat sebagai care giver dapat menerapkan oral care dan madu pada pasien anak untuk menjaga kelembaban membran mukosa oral akibat penggunaan NGT yang berlangsung lama. Kata Kunci: Anak, Gangguan Integritas Kulit, Penyakit Gaucher, Perawatan Mulut